BEAUTY BUZZ OR BUST? THE RISE AND FALL OF INFLUENCER MARKETING IN THE BEAUTY INDUSTRY AND ITS REAL IMPACT ON CUSTOMERS - O.A.Ashurbaev; A.M.Bakhromovna; A.M Baxadirovna; N.SH Baxtiyorovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Today, a single post on Instagram can make a product famous. Influencer marketing has become important to the beauty business and changed how brands connect with customers (Xu, 2023)[1] This article is focused on how influencer marketing has changed and influenced the Uzbekistan beauty industry. Most brands spend a lot of money just to keep up relations with influencers. This study aims to find out how these marketing tactics work on young female customers, particularly those aged between 15 to 40 or more. The purpose of this article is to explore both the benefits and drawbacks of influencer marketing for its ability to change people’s minds and behaviors. This study highlights how influencers increase the profile and credibility of a brand by sharing personalized beauty tips that work for them with their fans. However, it also goes on to discuss the negative aspects of this form of marketing about promoting false beauty standards and causing mental stress to young girls from such unreal images. The online survey with people from Uzbekistan is part of a quantitative research method used in an attempt to get as honest opinion as possible from customers regarding influencer marketing. The present study illustrates a range of reactions to material promoted by influencers, taking into consideration people of different ages, from naive teens to more informed consumers in their 30s and older.